From Bean to Biosphere: Vegetation Dynamics and Biodiversity in Arabica Coffee Agroforestry at Ijen Geopark - Dewi, Nilasari; Kurnianto, Agung Sih (Journal of Tropical Biodiversity and Biotechnology, 2025)
This study evaluates vegetation biodiversity and ecological conditions at the Bondowoso Biosite of Kebun Kopi, Ijen Geopark, to support sustainable Arabica coffee production. Three agroforestry plots (KR1-3) and a plantation plot (PN) were analyzed for species composition. In KR1, Acacia auriculiformis (IVI=110) and Trema orientalis (IVI=190) are prominent. KR2 is dominated by A. auriculiformis (IVI=160) and Ricinus communis (IVI=80), while Casuarina equisetifolia is significant in KR3. The PN plot shows a more even IVI distribution between Falcataria mollucana and Grevillea robusta. Tukey’s test reveals significant differences between KR1 and PN, and KR2 and PN plots (p-adj=0.001). The highest existence values are Anisoptera marginata (66.67%) in KR1, T. orientalis (53.33%) in KR2, C. equisetifolia (46.67%) in KR3, and Toona sureni (26.67%) in PN. Results indicate significant variations in species diversity, evenness, and dominance across plots, influenced by ecological, geographical, and anthropogenic factors. Higher Shannon-Wiener and Evenness indices in KR1 and KR2 suggest diverse species compositions are vital for ecosystem health, while KR3’s dominance of few species highlights the need for biodiversity conservation. This research recommends regenerative Arabica coffee farming practices and sustainable conservation strategies at the Bondowoso Biosite of Kebun Kopi.